Germination Behaviour of Chlorophora excelsa, (Welw.) Benth & Hook and Podocarpus usambarensis, Pilger - Chamshama, S. A. O.; Downs, R. J. (Indian Forester, 1982)
The effects of constant and alternating temperature light or dark on the germination of Chlorophora excelsa seeds and of mechanical and acid scarification on the germination of Podocarpus usambarensis seeds were studied. A temperature of 25°C in light, 30° in light and 30°/20°C in light or dark gave Significantly higher germination percentages in Chlorophora excelsa seeds, Germination was Significantly retarded by a constant temperature of 35°C in light and 30°C in dark. Complete removal of the seed coat resulted in 81% germination in Podocarpus usambarensis seeds, Mechanical scarification by seed coat removal at the radicle end of the seed Rnd concentrated sulphuric acid scarification for period. Up to 360 minutes resulted in nil germination after 6 weeks.